MODEL PAKET LAYANAN PENGUASAAN KONTEN BERTEMA KESIAPAN MENIKAH BERBASIS MULTIMEDIA PADA MAHASISWA - Sahara, Sanni (Indonesian Journal of Guidance and Counseling: Theory and Application, 2012)
Student is early adulthood has started the task of preparing for marriage and family life. Wedding preparations done to achieve the happy marriage. The role of aid agencies and universities such as PPLK-BK UNNES is needed. This can be done with the guidance and counseling services in the form of service-based interactive multimedia content mastery. Purpose of the study (1) know the profile of readiness married students, (2) to the hypothetical models (3) feasibility test results. The research method using Research and Development. Research on the final level UNNES 80 students who are not married to the purposive random sampling technique. Analysis technique that is descriptive method percentage. Married student readiness profile UNNES very problematic aspects of financial readiness. Multimedia is developed through the program and Adobe Flash CS4 Ms.Excel. The results include the results of model validation test instruments, test results of multimedia, the criteria for judicial review is appropriate, limited  utilities good  test  results so it is assumed can help students prepare for the wedding. Beharap authors of this study beneficial to the world of guidance and counseling at the college and the student help their wedding preparations.